A Review Study on Smart Water Bottle (International Journal of Innovative Research in Computer Science & Technology, 2021)
In today's ubiquitous IT environment,  even non-living objects interact with one another and  intelligently respond to changing circumstances. The  Internet of Things (IoT) is a new technology that  recognises and conceptualises the essence of computers.  The article provides a short overview of IoT-enabled  water bottles. Water is an essential component of human  existence. The quality of water is influenced by a number  of factors. The smart water bottle with touch and  photoplethysmographic sensors can accurately detect the  quantity of liquid in the bottle, monitor activity with  inertial sensors, and physiological characteristics with a  touch and photoplethysmographic sensor.The smart bottle  uses input sensors to continuously monitor these  parameters in real time; the system then analyses the data  and, if necessary, uses actuators to execute the  appropriate actions. In today's world, this method will be  beneficial to health-conscious people. This method may  also be very useful in the healthcare industry, where  additional caution is required in all areas.
Keywords: Health Care; IoT; Sensors; Waterbottle